Comparison of the effects of two different exercise programs on pain in subacromial impingement syndrome - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2009)
Objectives: We compared the effects of two different exercise programs below or above 90 degrees on pain in subacromial impingement syndrome (SIS). Methods: Thirty patients (23 females, 7 males; mean age 52 years; range 34-70) with acute or subacute SIS were randomly assigned to two groups, equal in number, to receive an exercise program below (group 1) or above (group 2) 90 degrees, respectively. In addition to the standard exercise program, transcutaneous electrical nerve stimulation, intermittent ultrasound, and cold pack were applied, and a nonsteroidal anti-inflammatory drug was given. Treatment lasted two weeks (10 sessions). Pain was assessed using the Constant score, a visual analog scale (VAS), and face score, and psychologic state was assessed with the Beck Depression Inventory. Satisfaction levels of the patients and the therapist were measured. Assessments were made before, and 2 and 16 weeks after treatment. Results: Both groups had significant improvements in the Constant score, VAS score, and face score at 2 and 16 weeks. Change in the face score between 2 and 16 weeks was not significant in croup 2. Improvements in the Beck Depression Inventory were significant in both groups. While patient satisfaction significantly increased in both groups, increase in the therapist's satisfaction between 2 and 16 weeks was significant only in group 1. The two groups did not differ with respect to changes in the Constant score, whereas VAS score at 2 weeks and face score at 16 weeks were significantly better in group 1. The two groups were similar with respect to improvements in the Beck Depression Inventory and patient/therapist satisfaction. Conclusion: The exercise program below 90 degrees (pain-free range of motion) resulted in additional improvements in VAS and face scores in SIS.
Keywords: Exercise therapy/methods; physical therapy modalities; shoulder impingement syndrome/rehabilitation; shoulder pain/rehabilitation; SHOULDER FUNCTION; CONVENTIONAL PHYSIOTHERAPY; SCALE